A field performance evaluation of the periodic maintenance for pervious concrete pavement. (1st August 2020) - Hu, Nian; Zhang, Jiong; Xia, Shuang; Han, Ruonan; Dai, Zhaoxia; She, Rui; Cui, Xinzhuang; Meng, Bowen
Abstract: The pores of pervious concrete pavement will be clogged by sediment carried by rainwater runoff and atmospheric deposition on the pavement in the course of using, thus reducing the permeability of pavement. It is necessary to adopt effective maintenance measures to keep the permeability of the pavement. In this study, an improved single ring infiltrometer is used to measure the permeability of a newly constructed pervious pavement. In order to study the deterioration process of the pavement permeability under periodic clogging maintenance conditions, four different gradations of clogging materials and eight different maintenance methods were used for 32 test cases. Different maintenance methods are designed to find the best combination, including different pressure wash, sweep + vacuum and pressure wash + vacuum. The study shows when the pressure wash is between 5 and 20Mpa, the maintenance effect has little difference, and the combination of pressure wash and vacuum suction has the best maintenance effect. Highlights: The permeability of pervious pavement will completely be lost after periodic clogging. Periodic maintenance can extend the service life of pervious pavement. Pressure wash + vacuum has the best maintenance effect. A fitted relationship is developed to evaluate the remaining permeability after certain periodic maintenances.